Nostalgia and Contemporary Spanish Narrative (XXI Century. Spanish Literature and Culture, 2004)
The Spanish Transition unravels a literary atmosphere of disenchantment in which, through areflective reading, we can see manifest with great care the nostalgia, the loss and the introspection. Be it‘renovating’, ‘dreaming’ or ‘thoughtful’ nostalgia, all of them create a personal dissatisfaction that theauthor labels as a state of madness, not sanity, in which his study is focused.
Keywords: Transition; Spanish narrative; reflection; madness; sanity